Aspects of Wear Mechanisms of Carbide Tools when Machine Hastelloy C-22HS - K., Kadirgama; M. M., Noor; B., Mohammad; H. H., Habeeb (2010)

(untitled)
In this study the performances of some commercially available carbide inserts when machining Hastelloy C-22HS was investigated under scanning electron microscopy (SEM) for wear mechanisms and other microstructure defects. Carbide inserts coated with TiCN/TiN and TiALN/ TiN experienced severe intergranular fractures and cracks. High temperature causes the layer of the coating to wear off and subsequently the inserts damaged at fast rates. Both types of inserts suffered from high crater wear and thermal cracking. Most of the wear occurred at the nose and flank of the inserts. Generally, it was observed that carbide coated with TiALN/ TiN cutting tool performed better than carbide coated TiCN/TiN cutting tool when milling Hastelloy C-22HS